Factors Associated with Ever Being HIV-Tested in Zimbabwe: An Extended Analysis of the Zimbabwe Demographic and Health Survey (2010-2011). - Kudakwashe Collin Takarinda; Lydia Kudakwashe Madyira; Mutsa Mhangara; Victor Makaza; Memory Maphosa-Mutsaka; Simbarashe Rusakaniko; Peter H Kilmarx; Tsitsi Mutasa-Apollo; Getrude Ncube; Anthony David Harries (PLoS ONE, 2016)
INTRODUCTION:Zimbabwe has a high human immunodeficiency virus (HIV) burden. It is therefore important to scale up HIV-testing and counseling (HTC) as a gateway to HIV prevention, treatment and care. OBJECTIVE:To determine factors associated with being HIV-tested among adult men and women in Zimbabwe. METHODS:Secondary analysis was done using data from 7,313 women and 6,584 men who completed interviewer-administered questionnaires and provided blood specimens for HIV testing during the Zimbabwe Demographic and Health Survey (ZDHS) 2010-11. Factors associated with ever being HIV-tested were determined using multivariate logistic regression. RESULTS:HIV-testing was higher among women compared to men (61% versus 39%). HIV-infected respondents were more likely to be tested compared to those who were HIV-negative for both men [adjusted odds ratio (AOR) = 1.53; 95% confidence interval (CI) (1.27-1.84)] and women [AOR = 1.42; 95% CI (1.20-1.69)]. However, only 55% and 74% of these HIV-infected men and women respectively had ever been tested. Among women, visiting antenatal care (ANC) [AOR = 5.48, 95% CI (4.08-7.36)] was the most significant predictor of being tested whilst a novel finding for men was higher odds of testing among those reporting a sexually transmitted infection (STI) in the past 12 months [AOR = 1.86, 95%CI (1.26-2.74)]. Among men, the odds of ever being tested increased with age ≥ 20 years, particularly those 45-49 years [AOR = 4.21; 95% CI (2.74-6.48)] whilst for women testing was highest among those aged 25-29 years [AOR = 2.01; 95% CI (1.63-2.48)]. Other significant factors for both sexes were increasing education level, higher wealth status and currently/formerly being in union. CONCLUSIONS:There remains a high proportion of undiagnosed HIV-infected persons and hence there is a need for innovative strategies aimed at increasing HIV-testing, particularly for men and in lower-income and lower-educated populations. Promotion of STI services can be an important gateway for testing more men whilst ANC still remains an important option for HIV-testing among pregnant women.